Arterial Hypertension in a Child with Williams-Beuren Syndrome (7q11.23 Chromosomal Deletion) - Sylos,Cristina de (2002)
We report the case of a 7-year-old male child diagnosed with Williams-Beuren syndrome and arterial hypertension refractory to clinical treatment. The diagnosis was confirmed by genetic study. Narrowing of the descending aorta and stenosis of the renal arteries were also diagnosed. Systemic vascular alterations caused by deletion of the elastin gene may occur early in individuals with Williams-Beuren syndrome, leading to the clinical manifestation of systemic arterial hypertension refractory to drug treatment.